The Insular Cortex and the Regulation of Cardiac Function. Issue 2 (15th March 2016) - Oppenheimer, Stephen; Cechetto, David
ABSTRACT: Cortical representation of the heart challenges the orthodox view that cardiac regulation is confined to stereotyped, preprogrammed and rigid responses to exteroceptive or interoceptive environmental stimuli. The insula has been the region most studied in this regard; the results of clinical, experimental, and functional radiological studies show a complex interweave of activity with patterns dynamically varying regarding lateralization and antero‐posterior distribution of responsive insular regions. Either acting alone or together with other cortical areas including the anterior cingulate, medial prefrontal, and orbito‐frontal cortices as part of a concerted network, the insula can imbue perceptions with autonomic color providing emotional salience, and aiding in learning and behavioral decision choice. In these functions, cardiovascular input and the right anterior insula appear to play an important, if not pivotal role. At a more basic level, the insula gauges cardiovascular responses to exteroceptive and interoceptive stimuli, taking into account memory, cognitive, and reflexive constructs thereby ensuring appropriate survival responses and maintaining emotional and physiological homeostasis. When acquired derangements to the insula occur after stroke, during a seizure or from abnormal central processing of interoceptive or exteroceptive environmental cues as in psychiatric disorders, serious consequences can arise including cardiac electrophysiological, structural and contractile dysfunction and sudden cardiac death. © 2016 American Physiological Society. Compr Physiol 6:1081‐1133, 2016.